The Effects of Sundanese Kacapi Suling â€œAyun Ambingâ€ Music Therapy to The Level of Anxiety on Chronic Renal Failure Patient Undergoing Hemodialysis - Mustopa Saepul Alamsah; Laili Rahayuwati; Chandra Isabella Hostanida Purba (JKP (Jurnal Keperawatan Padjajaran), 2018)
ABSTRACT Â